2016
DOI: 10.1016/j.techfore.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable water resource and endogenous economic growth

Abstract: Poyang Lake suffers from a severe shortage of water, due to the construction of the Three Gorges Dam and other hydropower stations along the upper Yangtze River. In this paper, we propose a two-sector endogenous growth model to investigate the effects of extractive water use and impoundment activities on the optimal sustainable growth path. To offset the negative impact of the extractive use on the regenerative capacities of water resources, the impoundment activities should grow at a constant rate. We also pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Endogenous power has less impact on the economy. Zhang et al [14] also found that when the endowment or the regenerative capacities of water resources are low, the long-run sustainable growth cannot be achieved without sufficient impoundment activities. And the optimal levels of extractive water use and activities should be mated, and the progress in water technological levels is one of the most effective ways.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Endogenous power has less impact on the economy. Zhang et al [14] also found that when the endowment or the regenerative capacities of water resources are low, the long-run sustainable growth cannot be achieved without sufficient impoundment activities. And the optimal levels of extractive water use and activities should be mated, and the progress in water technological levels is one of the most effective ways.…”
Section: Plos Onementioning
confidence: 99%
“…These theories were attractive due to their simplicity which typically included aggregate trend parameters to account for changes in all technologies, however, no mechanism explained how water technologies were developed and selected. Therefore, when addressing the problem of water resources scarcity, this framework was unable to answer how much water technological progress was needed to reduce water resources constraints and what water technological progress was needed to compensate for fading water resource inputs [14]. Given these conditions, it was necessary to introduce water technologies as an endogenous variable to theory of economic growth and thoroughly scrutinize the incentives.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Poyang Lake has suffered from a severe water shortage due to the lack of rainfall and the pollution from the UR, MR, and LR in addition to the interactive decision to construct dams or reservoirs among the regions [28]. This also shows that the government of the sub-reaches have applied to the central government for the construction of dams or reservoirs to solve the water shortage problem [2]. At the same time, the high cost of building dams and reservoirs means that if there is no restriction from the central government, the upper and middle reaches may obtain the power to use natural resources jointly and exclusively, which has a negative impact on other regions.…”
Section: Study Areamentioning
confidence: 99%
“…In recent years, water resource exploitation has been an important way to achieve regional development in many countries [1,2]. It has been reported that basins represent a special type of region with strong integrity and a high degree of correlation [3].…”
Section: Introductionmentioning
confidence: 99%
“…Urbanization has greatly increased productivity but has also brought many problems such as environmental degradation and economic inequality to China. Industrial production takes up a large amount of land resources, which causes problems such as relatively low resource utilization efficiencies and environmental degradation [1,2]. There are also problems in the utilization of industrial land, such as irrational land use structure, idle land, deferred use and low utilization efficiency [3].…”
Section: Introductionmentioning
confidence: 99%